Assessment of DRAINMOD-NII model for prediction of nitrogen losses through subsurface drained sandy clay under cultivation in south west Punjab, India. Issue 10 (9th September 2022) - Dar, Mehraj U Din; Singh, J. P.
Abstract: In the present study, the DRAINMOD-NII model was calibrated for the years 2018–2019 and validated for the period 2019–2020 over the two cropping years. The model simulations were statistically evaluated by comparing the measured drain flows and nitrate-nitrogen (NO3 -N) with the model simulated drain outflows and nitrate loss. The study results depicted closer agreement between the simulated and observed results for both the calibration and validation periods. The root mean square error (RMSE) of the drainage rate was 8.88 cm more than observed data, 15.41, 0.53 and 0.57 cm were the values recorded for PBIAS, modelling efficiency (NSE) and R 2 . The similar parameter values for nitrogen load were recorded to be 0.14, 2.76, 0.84 and 0.88 respectively during the calibration period for the rice-wheat system. The model was statistically tested during the validation period also, confirming DRAINMOD-NII has the capability to simulate nitrogen losses from the area subjected to subsurface drainage system. HIGHLIGHTS: Subsurface drainage system improves the soil conditions. The subsurface drainage system leads to excess nitrate loss to water bodies. Simulation models help to quantify the amount of nitrate being lost. This study will help in the design of more subsurface drainage systems in the Punjab state which is facing serious problems of waterlogging. Graphical Abstract